Meningkatkan Hasil Belajar Matematika di Sekolah Dasar melalui Model Pembelajaran Problem Based Learning - Nuryati, Arini Endah; Tryanasari, Dewi; Suprapti, Suprapti (Edusia: Jurnal Ilmiah Pendidikan Asia, 2022)
This research was conducted with the objectives of: (1) To describe how SDN Ngariboyo 4, Ngariboyo District, Magetan Regency uses the Problem-Based Learning (PBL) learning model to improve student learning outcomes in class V. 2) To describe the effect of increasing student learning outcomes in the Problem-Based Learning learning model ( PBL) class V at SDN Ngariboyo 4, Ngariboyo District, Magetan Regency. (3) Describe the effect of developing student creativity in the Problem-Based Learning (PBL) learning model for class V at  SDN Ngariboyo 4, Ngariboyo District, Magetan Regency. This activity uses a class action research model (PTK) and quantitative descriptive. This PTK step consists of 2 cycles, each completed in two days. The study participants were only fifth-grade students enrolled at SDN Ngariboyo 4, Ngariboyo District, Magetan Regency, semester II of the 2022/2023 school year. The instruments applied in the activity are interviews, documentation, and observation. At the same time, evaluation focuses on test-based and non-test-based processes and outcomes. The results showed that using Problem-Based Learning (PBL) improved fifth-grade students' learning outcomes at SDN Ngariboyo 4, Ngariboyo District, Magetan Regency. This can be seen in the development value, which increased sharply from the previous normal of 70.04 in cycle I and 79.04 in cycle II. The cycle ends when learning completeness reaches over 75% in cycle II. The effect of implementing Problem-Based Learning (PBL) learning can improve student learning outcomes, creativity, and activeness in experiences in the learning process.